STUDI KOMPARATIF KONSEP KEBAHAGIAAN MENURUT JOHN STUART MILL DAN AL-GHAZALI - Dina Aprilia; Nurhasanah Nurhasanah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The fundamental differences in the concept of happiness between John Stuart Mill and Al-Ghazali arise from distinct social, cultural, and philosophical contexts, raising questions about comparison and a holistic understanding of happiness as the ultimate goal of human life. This study aims to analyze and compare their concepts of happiness, in which Mill emphasizes utilitarianism oriented toward general happiness and the quality of individual pleasures, while Al-Ghazali focuses on spiritual and moral dimensions. The research method is a literature study with a comparative approach, utilizing primary and secondary sources such as Mill’s Utilitarianism and Al-Ghazali’s Ihya’ Ulum al-Din. The analysis is conducted by comparing their concepts of happiness, their implications for human life, and the socio-cultural contexts in which they emerged. The findings indicate a shared agreement that happiness constitutes the ultimate end of human life, despite differing approaches: Mill prioritizes individual freedom and the quality of happiness, whereas Al-Ghazali emphasizes spirituality and morality. The study recommends integrating utilitarian and spiritual perspectives to offer a holistic solution to the pursuit of happiness in modern society.